The role of national culture and lifestyle in shaping consumer behavior - Marinković Veljko; Lazarević Jovana; Šapić Srđan (Marketing (Beograd. 1991))
Contemporary marketing-oriented enterprises analyze the behavior of their target consumers by tracking the combined influence of various external and internal factors. The fundamental external determinant shaping consumer behavior is culture, while lifestyle stands out as one of the most significant internal determinants of consumption. Accordingly, the goal of the paper is to generate knowledge about national culture dimensions and consumer lifestyle influence on consumer behavior during the purchase decision-making process. For this purpose, 372 consumers were surveyed. The reliability analysis, confirmatory factor analysis, and Harman's one-factor test were conducted to assess model fit. The structural equation modeling was applied for hypothesis testing. The results of the conducted structural equation modeling confirm the national culture dimensions and lifestyle to be significant determinants of consumer behavior as they go through the purchase decision-making process. The paper's originality and contribution are related to the forming and empirical testing of an innovative, integrated research framework in the consumer behavior domain, as well as generating useful empirical knowledge that can serve managers and governments for formulating and implementing future business strategies.